(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Human resource is the people who make up the workforce of an organization. Indian banking sector comprises of private sector banks, public sector banks, cooperative banks, foreign owned banks and regional rural banks. The present study is an attempt to investigate the existing literature on HR practices of various Indian banks in Madhya Pradesh. HRM is the organizational function that deals with issues related to people such as, hiring, performance management, organization development, safety, wellness, benefits, employee motivation, communication, administration and training. In this paper light will be thrown on the concept, need of HR Department in Banks of Madhya Pradesh. It also focuses on the Concepts and Technique in HR Practices. Employee’s performance is the most important factor in an organization success, therefore, there is need to adopt effective human resources strategies that aim to improve employee’s performance and creates the culture of high performance in public and private sector banks based on human resource practices.